Method for evaluating imidization degree of high-pressure-resistant polyimide
Through Fourier infrared spectroscopy, the inaccuracy of the evaluation of the degree of imidation of polyimide films in the prior art is solved, and a multi-band comprehensive evaluation method is provided to ensure the high-thickness film Fully cured and high-voltage devices withstand voltage.
Patent Information
- Application Number
- CN202411461773.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art lacks fast, accurate and non-destructive methods to evaluate the degree of imidation of polyimide films, making it difficult to accurately judge the pressure resistance of the film, affecting the reliability and performance of high-voltage devices.
By preparing standard samples and experimental samples of different thicknesses, the absorption peak intensity of the sample in the imine I band, imine III band and benzene ring stretching vibration peak was analyzed using Fourier infrared spectrogram, and the degree of imine was calculated and compared. , provides a multi-band comprehensive evaluation method.
The accurate evaluation of the degree of imidation of polyimide films is achieved, ensuring sufficient curing of high-thickness films during high-temperature curing, and improving the voltage resistance and reliability of the device.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-voltage power device passivation layer manufacturing, and in particular relates to a method for evaluating the imidization degree of high-voltage withstand polyimide. Background Art
[0002] As the core component of high-voltage power applications, silicon carbide (SiC) power devices have shown great application potential in aerospace, new energy and other fields. However, the terminal discharge problem of such devices under high-voltage environments has always been a key factor restricting their widespread application. In order to improve the voltage resistance of the device, terminal passivation technology is widely used to reduce the electric field strength on the surface of the device. It is worth noting that the terminal electric field distribution of the device is not only affected by the terminal structure design, but also strongly depends on the characteristics of the surface passivation material used. Therefore, the reasonable selection and optimization of surface passivation materials are of vital importance to improving the voltage resistance level of the device.
[0003] Among many candidate materials, polyimide (PI) materials are highly favored due to their excellent insulation properties and good processability. In order to meet the requirements of high withstand voltage levels above 6kV, the thickness of the polyimide film needs to reach more than 20μm. However, this increase in thickness poses a challenge to the curing process of the film. The curing process of polyimide is essentially a process in which polyamic acid (PA) undergoes a dehydration cyclization reaction under heating conditions and is converted into polyimide, that is, the imidization process. The curing process of the film directly affects the degree of imidization of the material, and the degree of imidization is directly related to the pressure resistance of the film. During the high-temperature curing process, the removed water molecules escape in the form of water vapor, and a thicker film may make it difficult to completely discharge the internal water, which in turn affects the film's insufficient imidization reaction and low degree of imidization, which in turn affects the film's pressure resistance.
[0004] At present, the evaluation method for the imidization degree of polyimide films is still imperfect, and there is a lack of a fast, accurate, and non-destructive evaluation method. This makes it difficult to accurately determine the imidization degree of the film in practical applications, which in turn affects the reliability and performance of the device. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a method for evaluating the imidization degree of high-voltage polyimide. The evaluation method can quantitatively evaluate the imidization degree of the polyimide film through the absorption peak intensity ratio of the polyimide film at a specific wave number, so as to evaluate whether the imidization degree is sufficient when the thickness of the polyimide film is too high, and whether it can be used as a surface passivation layer of a high-voltage device.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for evaluating the imidization degree of high-voltage polyimide, comprising the following steps: S1: coating polyimide on a substrate by spin coating and baking to prepare a standard sample A and an experimental sample B, and then performing high temperature curing to obtain a fully cured standard sample A and a cured experimental sample B; wherein the thickness of the experimental sample B is greater than 20 μm, and the thickness of the standard sample A is less than the thickness of the experimental sample B; S2: Grinding the fully solidified standard sample A and the solidified experimental sample B with potassium bromide crystals to obtain a standard test sample A and an experimental test sample B; S3: Collect Fourier infrared spectra of standard test sample A and experimental test sample B, obtain and compare the absorption peak intensities of standard test sample A and experimental test sample B near imine I band and benzene ring stretching vibration peak to calculate the imidization degree R1 of the test sample; obtain and compare the absorption peak intensities of standard test sample A and experimental test sample B near imine III band and benzene ring stretching vibration peak to calculate the imidization degree R2 of the test sample; obtain the imidization degree R according to the imidization degrees R1 and R2 of the test sample.
[0007] In one embodiment, in S1, the substrate is a silicon-based substrate or a silicon dioxide deposited substrate; the baking temperature is 80° C. to 120° C., and the baking time is 20 min to 50 min.
[0008] In one embodiment, in S1, when preparing the standard sample A, the viscosity of the polyimide used is 3000 cp~8000 cp; when preparing the experimental sample B, the viscosity of the polyimide used is 10000 cp~18000 cp.
[0009] In one embodiment, the thickness of the standard sample A is 2 μm to 3 μm; the thickness of the experimental sample B is 30 μm to 60 μm.
[0010] In one embodiment, in S1, the high temperature curing of the standard sample A is a staged temperature increase curing carried out under a nitrogen atmosphere, the rate of the staged temperature increase curing is 5°C~10°C / min, and the temperature increase gradient of the staged temperature increase curing is: curing at 80°C~100°C for 20min~40min, curing at 100°C~150°C for 20min~40min, curing at 150°C~200°C for 30min~60min, curing at 200°C~250°C for 30min~60min, curing at 250°C~300°C for 0.5h~1h, and curing at 300°C~350°C for 2h~6h.
[0011] In one embodiment, in S1, the high temperature curing of the experimental sample B is a staged temperature increase curing carried out under a nitrogen atmosphere, the rate of the staged temperature increase curing is 5°C~10°C / min, and the temperature increase gradient of the staged temperature increase curing is: curing at 80°C~100°C for 20min~40min, curing at 100°C~150°C for 20min~40min, curing at 150°C~200°C for 30min~60min, curing at 200°C~250°C for 30min~60min, curing at 250°C~300°C for 0.5h~1h, and curing at 300°C~350°C for 1h~2h.
[0012] In one embodiment, in S3, the imine I band, imine III band, and benzene ring stretching vibration peaks are 1778 cm -1 、1376cm -1 、1490cm -1 .
[0013] In one embodiment, the formula for calculating the imidization degree R1 of the test sample is as follows: .
[0014] In one embodiment, the formula for calculating the imidization degree R2 of the test sample is as follows: .
[0015] In one embodiment, the imidization degree R is the average value of the sum of the imidization degrees R1 and R2 of the test samples.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for evaluating the imidization degree of high-voltage polyimide. By preparing standard samples A (thinner) and experimental samples B (thicker) of different thicknesses, standard sample A is a thinner sample and can be used as an evaluation benchmark after it is fully cured. Experimental sample B represents a difficult problem that needs to be solved in practical applications. By comparing it with the experimental sample B, the imidization degree and performance of the thicker film can be more accurately evaluated. In addition, this method not only focuses on a single absorption peak, but also comprehensively considers the information of multiple characteristic peaks of imine I band, imine III band and benzene ring stretching vibration peak. This multi-band comprehensive evaluation method can more comprehensively reflect the imidization degree of polyimide materials and reduce the error caused by the fluctuation of a single characteristic peak. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is the reaction formula of the imidization process of the polyimide of the present invention; Figure 2 is the Fourier infrared spectrum of the standard test sample A of the present invention; Figure 3 This is the Fourier infrared spectrum of the experimental test sample B of the present invention. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0019] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0020] In view of the challenges faced by traditional curing processes when polyimide films are thicker (especially above 20μm and in the range of 30μm to 60μm) in the manufacture of high-voltage power devices, namely, it is difficult to ensure that the film is completely cured and may affect its dielectric properties and stability in high-voltage applications, the method for evaluating the degree of imidization of high-voltage polyimide proposed in this application aims to evaluate the degree of curing of polyimide films through scientific and systematic means, to ensure that the film can still achieve an ideal cured state at a high thickness, and to meet the stringent requirements of high-voltage power devices.
[0021] The method for evaluating the imidization degree of the high-voltage polyimide comprises the following steps: S1: coating polyimide on a substrate by spin coating and baking to prepare a standard sample A and an experimental sample B, and then performing high temperature curing to obtain a fully cured standard sample A and a cured experimental sample B; wherein the thickness of the experimental sample B is greater than 20 μm, and the thickness of the standard sample A is much smaller than the thickness of the experimental sample B; for example, in one implementation process, the thickness of the standard sample A is 2 μm to 3 μm; the thickness of the experimental sample B is 30 μm to 60 μm, and in this embodiment process, the thickness of the experimental sample B is between 15 and 20 times the thickness of the standard sample A; S2: Grinding the fully solidified standard sample A and the solidified experimental sample B with potassium bromide crystals to obtain a standard test sample A and an experimental test sample B; S3: Collect Fourier infrared spectra of standard test sample A and experimental test sample B, obtain and compare the absorption peak intensities of standard test sample A and experimental test sample B near imine I band and benzene ring stretching vibration peak to calculate the imidization degree R1 of the test sample; obtain and compare the absorption peak intensities of standard test sample A and experimental test sample B near imine III band and benzene ring stretching vibration peak to calculate the imidization degree R2 of the test sample; obtain the imidization degree R according to the imidization degrees R1 and R2 of the test sample.
[0022] The above method prepares standard samples A (fully cured, as a reference) and experimental samples B (target thickness range) of different thicknesses by spin coating, ensuring the controllability and consistency of the experimental conditions. The absorption peak intensities of standard samples A and experimental samples B near imide band I, imide band III and benzene ring stretching vibration peaks are directly analyzed by Fourier transform infrared spectroscopy (FTIR). These characteristic peaks are closely related to the imidization degree of polyimide, so that the imidization degree of experimental sample B can be accurately reflected. By setting standard sample A as a fully cured reference, the influence of other factors on the results during the experiment can be eliminated, and the accuracy and reliability of the evaluation can be improved. This evaluation method is suitable for evaluating the imidization degree of thicker polyimide films, which solves the problem that traditional methods are difficult to accurately evaluate the curing state of high-thickness films. Due to the wide application of polyimide in high-voltage power devices, this evaluation method is of great significance for improving device performance and optimizing manufacturing processes, and has broad application prospects.
[0023] In a specific implementation, the specific process of S1 is as follows: S11: Spin coating a thin polyimide on a substrate and baking to form a thin film, which is referred to as standard sample A; spin coating a thick polyimide on a substrate and baking to form a thin film, which is referred to as experimental sample B; S12: Under a protective atmosphere, the standard sample A is cured at high temperature for a long time to ensure that the imidization reaction is sufficient, so as to obtain a completely cured standard sample A; under a protective atmosphere, the experimental sample B is cured at high temperature to obtain a cured experimental sample B.
[0024] Specifically, in S11, the substrate is a silicon-based substrate or a silicon dioxide deposited substrate; when preparing standard sample A, the viscosity of the polyimide used is 3000cp~8000cp; the baking temperature is 80℃~120℃, the baking time is 20min~50min, and the thickness of standard sample A is about 2μm~3μm.
[0025] In S12, Figure 1The reaction formula of the imidization process of polyimide shown in the figure and the high temperature curing process of standard sample A are as follows: Curing is carried out under a nitrogen atmosphere. The curing is a staged temperature rise curing with a heating rate of 5°C~10°C / min. The temperature rise gradient is: curing at 80°C~100°C for 20min~40min, curing at 100°C~150°C for 20min~40min, curing at 150°C~200°C for 30min~60min, curing at 200°C~250°C for 30min~60min, curing at 250°C~300°C for 0.5h~1h, and curing at 300°C~350°C for 2h~6h to ensure that the standard sample A is fully imidized.
[0026] Specifically, in S11, the substrate is a silicon-based substrate or a silicon dioxide deposited substrate; when preparing the experimental sample B, the viscosity of the polyimide used is 10000cp~18000cp; the baking temperature is 80℃~120℃, the baking time is 20min~50min, and the thickness of the experimental sample B is about 30μm~60μm.
[0027] In S12, Figure 1 The reaction formula of the imidization process of polyimide shown in the figure and the high temperature curing process of experimental sample B are as follows: The curing is carried out under a nitrogen atmosphere, and the curing is a staged temperature rise curing with a heating rate of 5°C~10°C / min, and a temperature rise gradient of: curing at 80°C~100°C for 20min~40min, curing at 100°C~150°C for 20min~40min, curing at 150°C~200°C for 30min~60min, curing at 200°C~250°C for 30min~60min, curing at 250°C~300°C for 0.5h~1h, and curing at 300°C~350°C for 1h~2h.
[0028] In one specific embodiment, the process of preparing the fully cured standard sample A and the cured experimental sample B is as follows: S11: A thin film of 2 μm thick polyimide with a viscosity of 3000 cp is coated on a silicon-based substrate by spin coating and baked at 80°C for 20 min to form a thin film, which is referred to as standard sample A; a thick film of 40 μm thick polyimide with a viscosity of 10000 cp is coated on a silicon-based substrate by spin coating and baked at 80°C for 20 min to form a thin film, which is referred to as experimental sample B; S12: Under a protective atmosphere, the standard sample A is cured at high temperature for a long time to ensure that the imidization reaction is sufficient, so as to obtain a completely cured standard sample A; under a protective atmosphere, the experimental sample B is cured at high temperature to obtain a cured experimental sample B.
[0029] When the above curing is performed, the following same curing method is adopted: The speed of the staged temperature rise curing is 5°C / min, and the temperature rise gradient of the staged temperature rise curing is: curing at 80°C for 20min, curing at 100°C for 20min, curing at 150°C for 30min, curing at 200°C for 30min, curing at 250°C for 0.5h and curing at 300°C for 1h.
[0030] It should be noted that when in the final stage of high-temperature curing, the curing time of standard sample A was extended, that is, it was cured for 2 h at a temperature of 300 °C.
[0031] In another specific embodiment, the process of preparing the fully cured standard sample A and the cured experimental sample B is as follows: S11: A thin film of 3 μm thick polyimide with a viscosity of 8000 cp is coated on a silicon dioxide deposition substrate by spin coating and baked at 120°C for 50 min to form a thin film, which is used as standard sample A; a thick film of 60 μm thick polyimide with a viscosity of 18000 cp is coated on a silicon dioxide deposition substrate by spin coating and baked at 120°C for 50 min to form a thin film, which is used as experimental sample B; S12: Under a protective atmosphere, the standard sample A is cured at high temperature for a long time to ensure that the imidization reaction is sufficient, so as to obtain a completely cured standard sample A; under a protective atmosphere, the experimental sample B is cured at high temperature to obtain a cured experimental sample B.
[0032] When the above curing is performed, the following same curing method is adopted: The speed of the staged temperature rise curing is 10°C / min, and the temperature rise gradient of the staged temperature rise curing is: curing at 100°C for 40min, curing at 150°C for 40min, curing at 200°C for 60min, curing at 250°C for 60min, curing at 300°C for 1h and curing at 350°C for 2h.
[0033] It should be noted that when in the final stage of high-temperature curing, the curing time of standard sample A was extended, that is, it was cured for 6 hours at a temperature of 350°C.
[0034] The above-mentioned staged temperature rise curing is carried out in a nitrogen atmosphere. High-temperature curing under nitrogen protection is a key step. The nitrogen atmosphere effectively prevents the possible oxidative degradation of polyimide at high temperature, thereby ensuring the stability of the curing process and the quality of the final product.
[0035] The above preparation process combines spin coating with staged temperature rise curing technology under nitrogen atmosphere. The polyimide is evenly and accurately coated on the substrate by spin coating, and then preliminarily baked to form a film. This process not only ensures the uniform distribution of polyimide, but also lays the foundation for its subsequent deep curing. The staged temperature rise curing method enables the polyimide to fully react and cross-link in different temperature ranges by accurately controlling the heating rate and the curing time of each temperature section. This fine curing control allows even thicker polyimide films to achieve ideal curing effects.
[0036] In S2, polyimide film samples A and B, namely, fully cured standard sample A and cured experimental sample B, are ground together with potassium bromide crystals respectively, and the dosage ratio of fully cured standard sample A and cured experimental sample B to potassium bromide crystals is 1:(100-200). Pressure is applied for tableting to prepare test samples, namely, standard test sample A and experimental test sample B.
[0037] In a specific embodiment, 1-50 mg of a fully cured standard sample A with a thickness of 2 μm is ground together with potassium bromide crystals to obtain a standard test sample A under pressure; 1-50 mg of a cured experimental sample B with a thickness of 40 μm is ground together with potassium bromide crystals to obtain an experimental test sample B under pressure, and Fourier infrared spectra of the standard test sample A and the experimental test sample B are collected.
[0038] In S3, the process of collecting the Fourier transform infrared spectra of the standard test sample A and the experimental test sample B is as follows: S31: Collect Fourier transform infrared spectra of the fully cured standard sample A and the cured experimental sample B by attenuated total reflectance (ATR); S32: Obtain and compare the absorption peak intensities of the standard test sample A and the experimental test sample B near the imine I band and the benzene ring stretching vibration peak to calculate the imidization degree R1 of the test sample; S33: Obtain and compare the absorption peak intensities of the standard test sample A and the experimental test sample B near the imine III band and the benzene ring stretching vibration peak to calculate the imidization degree R2 of the test sample; S34: Obtain the imidization degree R according to the imidization degrees R1 and R2 of the test sample.
[0039] Using attenuated total reflectance (ATR) to collect Fourier transform infrared spectra, no additional processing or damage to the sample is required, and in-situ detection can be performed directly on the sample surface. For thicker films, it may be difficult to completely discharge the internal moisture or other volatile components, thus affecting the uniformity and sufficiency of the imidization reaction. However, by mainly analyzing the sample surface information through ATR technology, the influence of internal factors on the test results can be relatively reduced, thereby more accurately reflecting the imidization degree of the sample surface.
[0040] In the spectrum of PI, 1495 cm -1 The strong absorption band at 1776cm is the benzene ring stretching vibration peak; -1 、1733cm -1 、1379cm -1 、726cm -1 The four absorption bands are characteristic absorption bands of polyimide, which are called imide band I, band II, band III, and band IV respectively.
[0041] In S32, the imine I band (1778 cm-1) of the standard test sample A and the experimental test sample B are obtained and compared. -1 )、benzene ring stretching vibration peak (1490cm -1 ) is used to calculate the imidization degree R1 of the test sample; The formula for calculating the imidization degree R1 of the test sample is as follows:
[0042] In S33, the imine III band (1376 cm-1) of the standard test sample A and the experimental test sample B are obtained and compared. -1 ), benzene ring stretching vibration peak (1490cm -1 ) is used to calculate the imidization degree R2 of the test sample; The formula for calculating the imidization degree R2 of the test sample is as follows:
[0043] In S34, the average value of the sum of the imidization degrees R1 and R2 of the test sample is obtained as the imidization degree R.
[0044] The formula for calculating the imidization degree R is as follows:
[0045] Infrared spectroscopy is very sensitive to the vibration of chemical bonds in molecules and can accurately identify and quantify specific functional groups in samples. By simultaneously measuring the absorption peak intensities near the imine band I, imine band III and benzene ring stretching vibration peak, and calculating the imidization degrees R1 and R2 respectively, a multi-band comprehensive evaluation of the imidization degree of the sample can be achieved. This multi-parameter evaluation method can more comprehensively reflect the chemical structure and performance changes of the sample and reduce the errors that may be caused by a single parameter. This multi-band comprehensive analysis method can more comprehensively reflect the chemical structure and performance changes of the sample, especially in the case of large thickness, and can more accurately evaluate the uniformity and sufficiency of the imidization of the sample. The accuracy of the evaluation can be further improved by calculating the average value of the sum of the imidization degrees R1 and R2 of the test sample as the final imidization degree R. This method takes into account the contribution of different band absorption peaks to the imidization degree and reduces the influence of accidental errors on the results.
[0046] In a specific implementation process, the imidization degree of high voltage-resistant polyimide is evaluated by using the following imidization degree evaluation method.
[0047] The Fourier infrared spectra of the fully cured standard test sample A with a thickness of 2 μm and the experimental test sample B with a thickness of 40 μm are collected as shown in the figure. Figure 2 and Figure 3 As shown, and according to both at 1778cm -1 、1490cm -1 and 1376cm -1 The imidization degree R of the test sample was calculated based on the absorption peak intensity near
[0048] According to the standard test sample A and the experimental test sample B at 1778cm -1 、1490cm -1 The imidization degree R1 of the test sample was calculated based on the absorption peak intensity near
[0049]
[0050]
[0051] According to the standard test sample A and the experimental test sample B at 1376cm -1 、1490cm -1 The imidization degree R2 of the test sample was calculated based on the absorption peak intensity near the
[0052]
[0053]
[0054] The final imidization degree R is obtained by calculating the average value of R1 and R2.
[0055]
[0056] Based on the evaluation method of the imidization degree R in the above embodiment, the imidization degree R of the high-voltage polyimide prepared by the above imidization method is evaluated. After the polyimide film is cured, its imidization degree is greater than 98%, the breakdown field strength is greater than 350V / μm, and the breakdown voltage is greater than 6kV.
[0057] It can be seen that the imidization method of the high-voltage polyimide can fully cure the polyimide of 30μm~60μm, the imidization degree reaches more than 98%, the breakdown field strength is greater than 350V / μm, and the breakdown voltage is greater than 6kV, so that it has good dielectric properties and can be used in the passivation layer of polyimide materials of high-voltage power devices.
[0058] The evaluation method provided in this application not only focuses on a single absorption peak, but also comprehensively considers the information of multiple characteristic peaks including imine I band, imine III band and benzene ring stretching vibration peak. This multi-band comprehensive evaluation method can more comprehensively reflect the imidization degree of polyimide materials and reduce the error caused by the fluctuation of a single characteristic peak.
[0059] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for evaluating the imidization degree of high-voltage polyimide, characterized in that: The following steps are involved: S1: coating polyimide on a substrate by spin coating and baking to prepare a standard sample A and an experimental sample B, and then performing high temperature curing to obtain a fully cured standard sample A and a cured experimental sample B; wherein the thickness of the experimental sample B is greater than 20 μm, and the thickness of the standard sample A is less than the thickness of the experimental sample B; S2: Grinding the fully solidified standard sample A and the solidified experimental sample B with potassium bromide crystals to obtain a standard test sample A and an experimental test sample B; S3: Collect Fourier infrared spectra of standard test sample A and experimental test sample B, obtain and compare the absorption peak intensities of standard test sample A and experimental test sample B near imine I band and benzene ring stretching vibration peak to calculate the imidization degree R1 of the test sample; obtain and compare the absorption peak intensities of standard test sample A and experimental test sample B near imine III band and benzene ring stretching vibration peak to calculate the imidization degree R2 of the test sample; obtain the imidization degree R according to the imidization degrees R1 and R2 of the test sample.
2. The method for evaluating the imidization degree of high-voltage polyimide according to claim 1, characterized in that: In S1, the substrate is a silicon-based substrate or a silicon dioxide deposited substrate; the baking temperature is 80° C. to 120° C., and the baking time is 20 min to 50 min.
3. The method for evaluating the imidization degree of high-voltage polyimide according to claim 1, characterized in that: In S1, when preparing the standard sample A, the viscosity of the polyimide used is 3000cp~8000cp; when preparing the experimental sample B, the viscosity of the polyimide used is 10000cp~18000cp.
4. The method for evaluating the imidization degree of high-voltage polyimide according to claim 1, characterized in that: The thickness of the standard sample A is 2 μm to 3 μm; the thickness of the experimental sample B is 30 μm to 60 μm.
5. The method for evaluating the imidization degree of high-voltage polyimide according to claim 1, characterized in that: In S1, the high temperature curing of the standard sample A is a staged temperature increase curing carried out under a nitrogen atmosphere, the speed of the staged temperature increase curing is 5°C~10°C / min, and the temperature increase gradient of the staged temperature increase curing is: curing at 80°C~100°C for 20min~40min, curing at 100°C~150°C for 20min~40min, curing at 150°C~200°C for 30min~60min, curing at 200°C~250°C for 30min~60min, curing at 250°C~300°C for 0.5h~1h, and curing at 300°C~350°C for 2h~6h.
6. The method for evaluating the imidization degree of high-voltage polyimide according to claim 1, characterized in that: In S1, the high temperature curing of the experimental sample B is a staged temperature increase curing carried out under a nitrogen atmosphere, the speed of the staged temperature increase curing is 5°C~10°C / min, and the temperature increase gradient of the staged temperature increase curing is: curing at 80°C~100°C for 20min~40min, curing at 100°C~150°C for 20min~40min, curing at 150°C~200°C for 30min~60min, curing at 200°C~250°C for 30min~60min, curing at 250°C~300°C for 0.5h~1h, and curing at 300°C~350°C for 1h~2h.
7. The method for evaluating the imidization degree of high-voltage polyimide according to claim 1, characterized in that: In S3, the imine I band, imine III band, and benzene ring stretching vibration peaks are 1778 cm -1 、1376cm -1 、1490cm -1 .
8. The method for evaluating the imidization degree of high-voltage polyimide according to claim 1, characterized in that: The formula for calculating the imidization degree R1 of the test sample is as follows: 。 9. The method for evaluating the imidization degree of high-voltage polyimide according to claim 1, characterized in that: The formula for calculating the imidization degree R2 of the test sample is as follows: 。 10. The method for evaluating the imidization degree of high-voltage polyimide according to claim 1, characterized in that: The imidization degree R is the average value of the sum of the imidization degrees R1 and R2 of the test samples.
Citation Information
Cited By
Method for detecting content of imide structure in photosensitive polyimide precursor resin
CN115791678A
Method for detecting imide structure content in photosensitive polyimide precursor resin
CN115791678B
A segmented quantitative method for improving the accuracy of testing the imidization degree of polyimide by infrared spectroscopy
CN122689702A
